Modeling the potential distribution of Valeriana carnosa Sm. in Argentinean Patagonia: a proposal for conservation and in situ cultivation considering climate change projections - Nagahama, Nicolas (2020)
Over recent years species distribution models have been used for the identification of suitable cultivation zones for native plant species. Valeriana carnosa is one of the most frequently used native plants in Patagonian popular medicine, its underground organs being obtained from natural populations. Considering the growing market demand, it is now necessary to design strategies for the cultivation and conservation of this valuable species. In this study, Ecological Niche Modeling (ENM) using the Maxent model was used to predict potential geographical distributions of V. carnosa under current and future climatic conditions and considering the projected climate changes for the next fifty years in Argentinean Patagonia. Results showed that by 2070 it is expected that 22 % of the area with climatic conditions suited to V. carnosa will be lost. Most of these areas lie in the steppe region, and the remaining geographic areas with suitable climatic conditions will be found mainly in the Cordillera and Pre-Cordillera regions. We identified five endangered V. carnosa populations in Patagonia. This study provides a novel tool for planning in situ cultivation of V. carnosa and preserving genetic material from endangered populations, considering the climate projections for the coming decades in Patagonia.